ANALISIS PENERAPAN METODE ACTIVITY BASED MANAGEMENT UNTUK MENINGKATKAN EFISIENSI BIAYA PRODUKSI PADA PT. PESONA ARNOS BETON GRESIK - Yusi Sri Ratih Ayu; Mulyanto Nugroho (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
In the industry competition and technological advances increasing, companies can increase their competitive advantage to manage operational costs well. The costs issued by the company must have value added for the company so that there is no waste of costs. Therefore, cost efficiency is very crucial for a company in order to maintain its sustainability of the company. Activity-based management is a technique for increasing efficiency. This research aims to implement activity-based management to increase the efficiency of PT. The Charm of Arnos Concrete Gresik. This research is descriptive and qualitative, using primary data from interviews. Research that is descriptive qualitative using primary data in the form of interviews. Research findings show that by implementing activity-based management in PT Pesona Arnos Beton Gresik, activities with a low amount of added value are obtained after being carried out by this method. Costs that do not have added value can be reduced so that there are cost savings. This still develops efficiency without negating the quality of service provided to consumers or customers.